2021
DOI: 10.1111/jfcj.12204
|View full text |Cite
|
Sign up to set email alerts
|

In Their Own Words: The Impact of Indirect Trauma Exposure on Judges Presiding Over Cases Involving Minors Involved in Sex Trafficking

Abstract: Though secondary traumatic stress has been researched extensively among professionals working with youth in diverse professions, there is limited information about judicial experiences working with trafficked youth. This qualitative study involves 82 interviews with juvenile and family court judges to understand the impact of indirect trauma exposure. Over 80% of respondents describe symptoms of secondary traumatic stress and countertransference responses. Notably, 20% with these symptoms also reported increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Utilization of emotional support coping was significantly associated with high levels of STS in this study, and this has been recognized as a protection against the harmful effects of indirect trauma and work stress by helping professionals detach and not bring work stress and related distress home with them (Cummings et al, 2020; Price and McCallum, 2015). Consistent with other research, organizational support has been found to be a significant factor in STS outcomes across studies (Slattery & Goodman, 2009; Sprang et al, 2021). Interestingly, in this study, STS-informed practices as measured by the STSI-OA were the strongest predictor of individual STS of any of the factors in the model.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Utilization of emotional support coping was significantly associated with high levels of STS in this study, and this has been recognized as a protection against the harmful effects of indirect trauma and work stress by helping professionals detach and not bring work stress and related distress home with them (Cummings et al, 2020; Price and McCallum, 2015). Consistent with other research, organizational support has been found to be a significant factor in STS outcomes across studies (Slattery & Goodman, 2009; Sprang et al, 2021). Interestingly, in this study, STS-informed practices as measured by the STSI-OA were the strongest predictor of individual STS of any of the factors in the model.…”
Section: Discussionsupporting
confidence: 88%
“…This finding is consistent with emerging small studies that indicate that working with individuals who have been trafficked for sex is a particularly challenging form of trauma work that involves exposure to individuals with high symptom acuity and few supportive resources (Kliner & Stroud, 2012; Sprang & Cole, 2018; Pascual-Leone et al, 2017). For example, the taxing nature of this work was especially evident in a qualitative study of judges who preside over cases involving minors who have been sex trafficked, some who described experiencing significant STS symptoms and countertransference responses (Sprang et al, 2021). Additionally, there is growing awareness of the increase in sex trafficking worldwide and the lack of coordinated services render this a critical public health issue that must be addressed to help those directly impacted as well as to stabilize and better support the workforce (Kenny et al, 2023; Tsutsumi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations